The Representation of Identity Black Community as Seen in The Novel Entitled “Sula” By Toni Morrison - Urip Wuriati; Widyahening, Evy Tri; Sumardiono, Sumardiono (ITScience (Information Technology and Science), 2025)
This study discusses about the representation of identity black community as seen in the novel “Sula” by Toni Morrison. This study focussed the struggle of the black community in the 20th century. In the novel “Sula” by Toni Morrison, where black community experiencing oppression by the dominant community in every day life. This study used Principle Critical Race Theory by Richard Delgado and Jean Stefancic (2017) for the analysed representation of identity namely, 1) Racism is Ordinary, 2) Interest Convergence, 3) The Social Construction of Race, 4) Intersectionality, and 5) The Voice of people color. The result this study, the representation of identity depicted in the injustice, hope for freedom, and rebellion against the norms that existed in black society. The conclusion this novel depicting identity shape individual experiences of black people. Furthermore, this novel filled insights into struggle, thought, betrayal, and finding for identity the black people in the 20th century.